A Survey of Phytopathogenic Fungi and Oomycetes in Riyadh, Saudi Arabia - Arya Widyawan; Boy Valenza Damiri; Adyatma Irawan Santosa; Haris Setyaningrum (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2015)
A survey of phytopathogenic fungi and Oomyceteswas conducted in Riyadh, Kingdom of Saudi Arabia duringOctober 2008 – May 2009. Total of 223 samples were collectedfrom four regions; Al-Kharj, Oyaynah, Old Diriyah, and Al Amariyah. Isolation was done using Potato Dextrose Agar(PDA). Infected parts were cut then sterilized in chlorox(10%), then were put in petridish that contain PDA andincubated at 25-27 °C. A total twelve genera of fungi andsingle genera of Oomycetes were isolated from the infectedplants and identifi ed as Fusarium spp., Alternaria spp.,Helmintosphorium (Bipolaris) spp., Sclerotium spp., Rhizoctoniaspp., Cladosporium spp., Mauginiella scattae, Erysiphe spp.,Leveillula spp., Macrophomina phaseolina, Ustilago spp.,Ulocladium spp., and Phytium spp.